Study on the Speed Stability of Wheel Drive Mechanism used in Lunar Rover - Xiao Jie; Zeng Lingbin; Zhang Xiaowei; Liu Dianfu; Zou Huaiwu (Jixie chuandong)
The 3-stage planetary reducer with closed-loop control is adopted in CE-3 lunar rover wheel drive mechanism.Aiming at the problem that the speed stability of drive mechanism does not satisfy the design requirements,the factors affecting the speed stability of planetary reducer are systematically analyzed,and methods and measures minimizing the inequality of load sharing of planetary gear sets are studied carefully.Through troubleshooting and numerical simulations,the causation is uncovered as follows:the first stage sun gear radial runout exceeds the allowed range.Then two solutions are proposed:the first one is to redesign the first stage sun gear into a floating sun gear,the second one is to improve the machining precision of the first stage sun gear.And the second solution is adopted because it is smaller and lighter than the first one.Then much ground simulation tests which are conducted at the room condition,high-temperature vacuum condition and low-temperature vacuum condition demonstrate that the speed stability of drive mechanism satisfies the design requirements.At last,the effectiveness of the proposed method is validated by the telemetry parameters of lunar rover moving on the moon surface.